CORRUPTION: CONCEPT, SIGNS, TYPES. - G.K. Shagilova; S.I. Bakhiyev (Western European Studies, 2024)
(The word corruption is known to everyone, I emphasized in this article that such a concept of corruption and its signs and types are known that today the concept of corruption is used in all countries, and I emphasized that in Uzbekistan there were laws and regulations on combating corruption, and in this article a lot of information and the concept of corruption are given.)
Keywords: public administration; civil service; corruption; anti-corruption